1962
DOI: 10.2307/2394742
|View full text |Cite
|
Sign up to set email alerts
|

The Floral Morphology of Secamone and the Evolution of the Pollinating Apparatus in Asclepiadaceae

Abstract: The floral anatomy and morphology of several species of Secamone is discussed. Ontogenetic studies reveal that the anthers are 4-Ioculan In this respect Secamone differs from other members of the subfamily Cynanchoideae of Asclepiadaceae. The bilocular anthers of other Cynanchoideae are a result of phylogenetic suppression of the two outer locules of each anther, as shown by ontogenetic studies and by the origin and nature of the tapetal tissue. Ontogeny of the pollinum sacs is followed in Secamone. Pollen mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

1976
1976
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 22 publications
1
24
0
1
Order By: Relevance
“…Because it was unnamed, the status of this third group was ambiguous, and it was therefore subsumed in the Cynanchoideae (= Asclepiadoideae) in subsequent classifications by some authors (Bentham, 1876;Schumann, 1895). More commonly, however, it has been given equal rank (Endlicher, 1838;Decaisne, 1844;Safwat, 1962;Bruyns & Forster, 1991;Liede & Albers, 1994).…”
Section: Recognition Of the Secamonoideaementioning
confidence: 99%
See 1 more Smart Citation
“…Because it was unnamed, the status of this third group was ambiguous, and it was therefore subsumed in the Cynanchoideae (= Asclepiadoideae) in subsequent classifications by some authors (Bentham, 1876;Schumann, 1895). More commonly, however, it has been given equal rank (Endlicher, 1838;Decaisne, 1844;Safwat, 1962;Bruyns & Forster, 1991;Liede & Albers, 1994).…”
Section: Recognition Of the Secamonoideaementioning
confidence: 99%
“…They are clearly more similar to each other than to the rest of the Gentianales, and in a number of characters there is a gradation from the Apocynaceae to the Asclepiadaceae. Three suggestions for recognition and expression of this relationship have appeared: as one family (Hallier, 1905;Demeter, 1922;Safwat, 1962;Stebbins, 1974;Stevens, 1976;Thome, 1976Thome, , 1992Judd et al, 1994;Struwe et al, 1994;Takhtajan, 1997); as an order separate from the Gentianales (Tsiang, 1934;Hutchinson, 1973); and as a suborder within the Gentianales (Rosatti, 1989;Nicholas & Baijnath, 1994;Omlor, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted, however, that the sparse sampling in the present study may obscure homoplasious convergence to apical attachment among clades coded as uniformly basal reversal to basal attachment in Ascleoiadaceae (Endress and Bruyns, 2000). A rigorous basis for assessing the homology of ambiguous cases would be a comperative ontogenetic study of polinaria (Safwat, 1962, Kunze, 1993.…”
Section: Hemidesmus Indicus (L) R Br (Fig 12)mentioning
confidence: 89%
“…Corolline coronas have been considered to be prevalent in Periplocoideae, but very uncommon in Asclepiadoideae (kunze, 1990; Nilsson et al, 1993). They have been reported from Secamonoideae, but their distribution in this subfamily has been little discussed (Safwat, 1962;kunze, 1990). Corolline coronas are also found widely among non-asclepiad Apocynaceae (kunze, 1990; Endress and Bruyns, 2000).…”
Section: B2 Corolline Coronamentioning
confidence: 99%
“…The families Asclepiadaceae and Apocynaceae have been kept separate in most systems. Proposals to unite them were made by Demeter (1922), Safwat (1962), Thome (1992) and Struwe et al ( 1994). In a recent study, using rbcL sequence data, Sennblad & Bremer (1996) showed that the position of the Asclepiadaceae within the Apocynaceae is well supported, and therefore recommended the amalgamation of the two families.…”
mentioning
confidence: 99%